The relationship between moral courage, team work, and safe nursing care in clinical nurses: a multicenter cross-sectional study in Iran - Zahra Azizi; Mohammad Mehdi Naghizadeh; Mostafa Bijani (BMC, 2024)
Abstract Background Moral courage and team work are the most important aspects of professional competence in clinical nurses; nurses with moral courage and team work are thought to be able to deliver safe nursing care to patients. The present study aimed to investigate whether moral courage and teamwork correlate with safe nursing care among clinical nurses. Methods This descriptive cross-sectional multicenter study was carried out from December 2023 to February 2024. A total of 375 nurses who were practicing in four hospitals in the south of Iran were enrolled in this study using convenience sampling. The data collection tools used consisted of a demographics survey, Moral Courage Questionnaire (MCQ), Team STEPPS Team Perception Questionnaire (T-TPQ), and the Assessment of Safe Nursing Care Questionnaire (ASNCQ). The data were analyzed using descriptive statistics, t-test, chi-square, multiple regression analysis, and Pearson's correlation coefficient. SPSS version 22 was used to analyze the data. Results The participants' mean age was 32.66 ± 6.63 years, and their work experience was 8.56 ± 6.22 years. The total mean scores for moral courage, teamwork, and safe care were 422.37 ± 52.92, 144.09 ± 18.43, 315.84 ± 41.95, respectively. A statistically significant positive correlation was found between teamwork and safe care (r = 0.57, p < 0.001), teamwork and moral courage (r = 0.49, p = 0.002), and moral courage and safe nursing care (r = 0.59 p < 0.001). According to the results, work experience, moral courage, and teamwork explained 44.4% of the variance in safe nursing care (R2 = 0.44, p < 0.001). Conclusion The results indicated that the moral courage and teamwork of nurses were positively and significantly correlated with the participants' safe nursing care. Accordingly, since moral courage and teamwork are the qualities that can contribute to improving the quality of care and ensuring safe nursing care, it is recommended that nursing managers pay special attention to these factors.